Design of Transmission Line Tower and Its Performances - Mohd Zulkifli, Mohd Shafiq (Universiti Teknologi Petronas, 2011)
Many tower failure cases are reported due to several conditions such as broken wire condition, earth wire broken, vandalism and also earthquake. The lower failures can be avoided by identifying the damage mechanism and improving the tower design. The tower can be designed using different codes of practices. However, currently, there is no comparison being made regarding the load acting on tower bodies if the tower design according to different codes of practices.